IMPACT OF ORGANIC AMENDMENTS ON BULB YIELD AND SOIL PARAMETERS OF GARLIC ( ARLIC (Allium sativum L.) FIELD CROP - VIKRAM SINGH; H. R. SHARMA (The Bioscan, 2019)
An experiment on organic amendments in garlic was conducted. Among treatment, T 4 90% RDN (Recommended doses of nutrients applied through FYM, Vermicompost, Sheep and Goat manure) + Panchagavya (5%) + Jeevamrut (5%) was found superior in bulb yield (98.54 q / ha), OC (1.66), available N (356.33 kg/ha), available P (53.50 kg/ha) and available K (443.00 kg/ha). Therefore the developed nutrient module emphasized in T 4 may be adopted and recommended in garlic crop getting for higher productivity and as well as sustained soil health.